Assessment of Factors Affecting the Implementation of Integrated Management of Neonatal and Childhood Illness for Treatment of under Five Children by Health Professional in Health Care Facilities in Yifat Cluster in North Shewa Zone, Amhara Region, Ethiopia - Ayele Mamo Abebe; Mesfin Wudu Kassaw; Fikir Alebachew Mengistu (International Journal of Pediatrics)
Background. Every year some 12 million children in developing countries die before they reach their fifth birthday. Seven in ten of these deaths are due to acute respiratory infections (mostly pneumonia), diarrhea, measles, malaria or malnutrition. The WHO Department of Child and Adolescent Health and Development (CAH), in collaboration with eleven other WHO programmes and UNICEF, has responded to this challenge by developing the Integrated Management of Childhood Illness (IMCI) strategy. Research that examines assessment of factors influencing the implementing the integrated management of neonatal and childhood illnesses (IMCI) strategy in Ethiopia is limited. Objective. To assess factors influencing the implementation of the IMNCI strategy by health professionals in public health institutions of Yifat cluster in North Shewa zone, Ethiopia, 2018. Method. An institutional based cross-sectional study will be conducted from March to May. A total of 201 health professionals will be selected using proportionally allocated to population size and interviewed using structured and pretested questionnaires. Data will be coded, entered and cleaned using SPSS version 20 for analysis. Univariate (frequency), Bivariate, Multiple logistic regression analysis will be employed. P-value and 95% confidence interval (CI) for OR will be used in judging the significance of the associations. P-value less than 0.05 will be taken as significant association. Results. Data were obtained from 201 health care professionals, yielding a response rate of 100%. The overall IMNCI implementation was 58% as high level implementation and 42% as low level implementation. In multivariate analysis the implementation of IMNCI was higher among IMNCI trained health care professionals ([AOR=2.7, 95% CI: (1.1.278, 4.562)]) and among those whose always referring chart booklet [AOR=2.76, 95% CI: (1.753, 5.975)]. Conclusion. IMNCI strategy can be better implemented through provision of training for the health workers. However, a variety of factor found to be a barrier to IMNCI implementation in a consistent way. Recommendations have been made related to provision of the training to the nurses and Health Care system strengthening among others.